2015
DOI: 10.1016/j.tourman.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Does ownership matter in publicly listed tourism firms? Evidence from Jordan

Abstract: This paper aims to provide new evidence on the relationship between ownership structure and firm performance. Unlike the previous empirical studies in the area of firm performance, we examine this relationship within a unique setting of publicly listed tourism firms. Our contribution is extended by investigating this relationship in Jordan as an emerging market and a famous tourist destination in the region. This is an interesting setting since ownership is more concentrated in the investigated firms. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…Empirical studies on corporate governance in the tourism sector focus on a variety of aspects. Aspects examined frequently include board composition, CEO duality, managerial ownership, and foreign institutional investors (Al‐Najjar, , ; M. H. Chen, Hou, & Lee, ; M. H. Chen, Kim, & Liao, ; Ozdemir & Upneja, ; C. M. Yeh, ; C. M. Yeh & Trejos, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Empirical studies on corporate governance in the tourism sector focus on a variety of aspects. Aspects examined frequently include board composition, CEO duality, managerial ownership, and foreign institutional investors (Al‐Najjar, , ; M. H. Chen, Hou, & Lee, ; M. H. Chen, Kim, & Liao, ; Ozdemir & Upneja, ; C. M. Yeh, ; C. M. Yeh & Trejos, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Leung and Lee () investigated listed tourism firms in the United States and found that the relationship between the level of institutional ownership and Monday stock return was positive. On the other hand, Al‐Najjar () used a sample of Jordanian listed tourism firms. He discovered a negative association between the presence of institutional shareholders and either return on asset (ROA) or return on equity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of previous economic research conducted in 2013 by The World Travel and Tourism Council was to highlight the importance of the tourism industry in Jordan (Jordan, Vogt, Kruger, & Grewe, 2013). The Ministry of Tourism and Antiquities in Jordan claimed that the industry's beneficence was USD6.6 trillion in GDP and represented 9% of the overall GDP (Al-Najjar, 2015).…”
Section: Introductionmentioning
confidence: 99%